The Role of Carbon Risk, Climate Change Exposure and Good Corporate Governance in The Cost of Capital - Nurnaningsih Utiarahman; Fahrudin Zain Olilingo; Raflin Hinelo; Robiyati Podungge (Journal of International Conference Proceedings, 2026)
This study examines the influence of carbon risk, climate change exposure, and good corporate governance on the cost of capital in manufacturing companies that go public on the IDX. This study uses a quantitative research approach using secondary data obtained from manufacturing companies that go public on the IDX. The sample consists of 100 observations of manufacturing companies that go public on the IDX, which were selected through purposive sampling. Data analysis was carried out using SPSS"26. Analysis techniques include descriptive statistics, classical assumption tests, multiple linear regression analysis, t-tests, F tests, and hypothesis testing. Partial results show that carbon risk, climate change exposure, and good corporate governance have a partial effect on the cost of capital in manufacturing companies that go public on the IDX. At the same time, carbon risk, climate change exposure, and good corporate governance affect the cost of capital in manufacturing companies that go public on the IDX. The study contributes to the accounting literature and provides practical implications for regulators, managers and investors